Early Removal of the Etonogestrel Contraceptive Implant and Associated Factors Among Users at the Urban Family Planning Clinic in Siriraj Hospital, Bangkok, Thailand - Parkpinyo, Nichamon; Panichyawat, Nalinee; Sirimai, Korakot (Siriraj Medical Journal, 2021)
Objective: To study the rate and reasons for the early removal of etonogestrel contraceptive implants and associated factors at the family planning clinic in Siriraj Hospital. Materials and Methods: This retrospective cohort study was conducted between May 2015 and December 2019 and contained 1,030 women who received the etonogestrel contraceptive implant. The medical records of demographic characteristics and clinical factors i.e., implant insertion date, implant removal date, reason for implant removal, contraceptive use before implant insertion and after implant removal, documented bleeding pattern and acceptability, were identified. Results: The mean age of participants was 28.6 ± 6.9 years. About 21% of women (218/1030) prematurely discontinued their etonogestrel implant. A desire to become pregnant was the most common reason for early removal of the etonogestrel implant (32%). Meanwhile, the most common side-effect contributing to early removal was unscheduled bleeding. The associated variables of early etonogestrel implant removal were low BMI (p-value = 0.021) and unacceptability of bleeding pattern at one year (p-value < 0.001) and two years (p-value < 0.001) after insertion. Conclusion: Early etonogestrel implant discontinuation rate was remarkable and the main reasons for it include a desire to become pregnant and bleeding side effects. Moreover, a lower BMI and unacceptability of bleeding problems also increased the likelihood of early removal of this contraceptive method.